Emotion Regulation Strategies of University Students in Coping with the Impostor Syndrome: A Systematic Review - Cantika Putri Nindita; Kinanti Dwi Restika; Alsyabilla Sekarkinasih Virenlish; Donny Hendrawan (Faculty of Psychology, Universitas Medan Area, 2026)
This systematic literature review synthesizes emotion regulation strategies that help students cope with impostor feelings, with a focus on cognitive reappraisal. A PRISMA 2020 guided search was conducted across multiple databases from November 2024 to December 2024. Eight studies met the inclusion criteria after title and abstract screening and full text assessment. The included evidence used quantitative, qualitative, and mixed method designs and represented 2400 participants aged 18 to 38 from several countries and academic disciplines. The synthesis indicates that cognitive reappraisal is most explicitly supported in educational and wellness interventions that train students to reinterpret failure, feedback, and achievement through structured reflection and evidence based self talk. The benefits of reappraisal tend to be stronger when supported by self compassion, which reduces self criticism. Interpersonal resources, especially peer and mentor support and inclusive communities, also contribute by strengthening belonging and stabilizing self evaluation in demanding academic contexts. Situation modification and task management strategies, such as planning routines and structured online modules, further support reductions in impostor experiences and related academic difficulties. These findings suggest that campus programs combining reappraisal training, self compassion skills, and sustained social support may help protect student mental health and academic persistence.